Antimicrobial Efficacy of Various Essential Oils at Varying Concentrations against Periopathogen Porphyromonas gingivalis - Hans, Veenu Madaan (J Clin Diagn Res, 2016)
INTRODUCTION: Porphyromonas gingivalis (P.gingivalis) is a notorious perio-pathogen with the ability to evade host defense mechanism and invade into the periodontal tissues. Many antimicrobial agents have been tested that curb its growth, although these agents tend to produce side effects such as antibiotic resistance and opportunistic infections. Therefore search for naturally occurring anti-microbials with lesser side effects is the need of the hour. AIM: The aim of this study was to substantiate the antimicrobial activity of various essential oils; eucalyptus oil, chamomile oil, tea tree oil and turmeric oil against P. gingivalis. MATERIALS AND METHODS: Pure cultures of P. gingivalis were grown on selective blood agar. Antimicrobial efficacy of various concentrations of essential oils (0%, 25%, 50% and 100%) was assessed via disc diffusion test. Zone of inhibition were measured around disc after 48 hours in millimeters. RESULTS: Zones of inhibition were directly proportional to the concentration of essential oils tested. At 100% concentration all the tested oils possess antimicrobial activity against P.gingivalis with eucalyptus oil being most effective followed by tea tree oil, chamomile oil and turmeric oil. CONCLUSION: All essential oils tested were effective against P.gingivalis. After testing for their clinical safety they could be developed into local agents to prevent and treat periodontitis.